2017
DOI: 10.1007/s00403-017-1778-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of bullous pemphigoid in Sweden 2005–2012: a nationwide population-based cohort study of 3761 patients

Abstract: Studies that report the incidence of bullous pemphigoid from validated nationwide population-based registries are rare. The aim of this study was to estimate the incidence of bullous pemphigoid in Sweden 2005–2012. A population-based open cohort study was designed including all patients diagnosed by a dermatologist with bullous pemphigoid (BP) in Sweden from 2005 to 2012 (n = 3761), identified from the National Patient Register (NPR). The diagnosis of bullous pemphigoid in the NPR was recently validated from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 31 publications
7
31
0
Order By: Relevance
“…A few epidemiological studies from the USA, Europe and Far East showed that the age‐specific incidence rate of BP increased markedly after 80 years of age . In our study, patients with coexisting BP and psoriasis were significantly younger than BP patients among the non‐exposed group.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…A few epidemiological studies from the USA, Europe and Far East showed that the age‐specific incidence rate of BP increased markedly after 80 years of age . In our study, patients with coexisting BP and psoriasis were significantly younger than BP patients among the non‐exposed group.…”
Section: Discussionsupporting
confidence: 45%
“…A few epidemiological studies from the USA, Europe and Far East showed that the age-specific incidence rate of BP increased markedly after 80 years of age. 19,20 In our study, patients with coexisting BP and psoriasis were significantly younger than BP patients among the non-exposed group. Moreover, among psoriatic patients, BP occurred not only in old age, but was also found in those aged less than 60 years, an age group in which BP has not been reported to occur frequently.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The incidence of BP in Europe is estimated to be 2.5-42.8 cases/million/year [3][4][5][6][7][8][9], with incidence increasing over the past eight decades [10] and a nearly 300-fold increase in those over age 90 compared to those younger than 60 [4]. This rise may reflect increasing average life expectancy, increasing use of polypharmacy, and improved detection and diagnosis [5].…”
Section: Introductionmentioning
confidence: 99%